Application of projection image of end mill to monitor its behaviour. (7th February 2007) - Dunwen, Zuo; Yoshihiro, Kawano
End mills with smaller diameter have found their wide application with the development of high-speed cutting. It becomes more and more important to develop effective methods to monitor and control the milling process with small end mills. In this paper, a measuring system of projection image for small end mills is introduced, and the application of the projection image to monitor the behaviour of the end mill is discussed. It is found that for static state of φ2 mm end mill, the measurement accuracy of its image width can be easily controlled within 1 μm. When the end mill rotates, it is not so difficult to control the accuracy within 3 μm. By using the change in the image width, the radial wear of the end mill can be estimated. On the other hand, if the centre shift of the image is premeasured the deflection of the end mill during cutting can be estimated.